A new species of sardine, Sardinella electra (Teleostei: Clupeiformes: Clupeidae), from the Ryukyu Islands, Japan - Hata, Harutaka; Motomura, Hiroyuki (Zootaxa, 2019)
A new species of sardine, Sardinella electra, is described on the basis of 18 specimens collected from the Ryukyu Islands, Japan. The new species closely resembles Sardinella hualiensis (Chu & Tsai 1958) in that both species have a caudal fin with black tips, a black spot on the dorsal-fin origin, and both have lateral scales with centrally continuous or overlapping longitudinal striae. However, the new species is distinguished from S. hualiensis by its higher total gill-raker counts on the first, second, third and fourth gill arches, and on the posterior face of the third gill arch (105–121, 107–120, 88–104, 65–82, and 25–31, respectively, vs. 87–107, 83–105, 67–90, 53–69, and 13–27), and in having scales with few perforations and lacking pores posteriorly (vs. scales with numerous perforations and pores on their posterior margins).